Angiotensin-(1-7) through Mas receptor up-regulates neuronal norepinephrine transporter via Akt and Erk1/2-dependent pathways - Lopez Verrilli, María Alejandra (2012)
As angiotensin (Ang) (1-7) decreases norepinephrine (NE) content in the synaptic cleft, we investigated the effect of Ang-(1-7) on NE neuronal uptake in spontaneously hypertensive rats. [ 3H]-NE neuronal uptake was measured in isolated hypothalami. NE transporter (NET) expression was evaluated in hypothalamic neuronal cultures by western-blot. Ang-(1-7) lacked an acute effect on neuronal NE uptake. Conversely, Ang-(1-7) caused an increase in NET expression after 3 h incubation (40 ± 7%), which was blocked by the Mas receptor antagonist, a PI3-kinase inhibitor or a MEK1/2 inhibitor suggesting the involvement of Mas receptor and the PI3-kinase/Akt and MEK1/2-ERK1/2 pathways in the Ang-(1-7)-stimulated NET expression. Ang-(1-7) through Mas receptors stimulated Akt and ERK1/2 activities in spontaneously hypertensive rat neurons. Cycloheximide attenuated Ang-(1-7) stimulation of NET expression suggesting that Ang-(1-7) stimulates NET synthesis. In fact, Ang-(1-7) increased NET mRNA levels. Thus, we evaluated the long-term effect of Ang-(1-7) on neuronal NE uptake after 3 h incubation. Under this condition, Ang-(1-7) increased neuronal NE uptake by 60 ± 14% which was blocked by cycloheximide and the Mas receptor antagonist. Neuronal NE uptake and NET expression were decreased after 3 h incubation with an anti-Ang-(1-7) antibody. Ang-(1-7) induces a chronic stimulatory effect on NET expression. In this way, Ang-(1-7) may regulate a pre-synaptic mechanism in maintaining appropriate synaptic NE levels during hypertensive conditions.